Ambipolar transition voltage spectroscopy: analytical results and experimental agreement - Bâldea, Ioan (Physical review. B, Condensed matter and materials physics, 2012)
This work emphasizes that the transition voltages Vt± for both bias polarities (V ≷ 0) should be used to properly determine the energy offset ɛ0 of the molecular orbital closest to electrodes’ Fermi level and the bias asymmetry γ in molecular junctions. Accurate analytical formulas are deduced to estimate ɛ0 and γ solely in terms of Vt±. These estimates are validated against experiments, by showing that full experimental I-V curves measured by Beebe et al. [Phys. Rev. Lett. 97, 026801 (2006)] and Tan et al. [Appl. Phsy. Lett. 96, 013110 (2010)] for both bias polarities can be excellently reproduced.